Learning Innovations During the Pandemic in Improving the Quality of Geography Learning - Anwar Shidiq Santoso (research, training and philanthropy institution Natural Aceh, 2021)
The COVID-19 pandemic outbreak has had a serious impact on the education system. Usually, learning is done face-to-face, but with the COVID-19 pandemic learning must be done remotely. Changes in learning patterns require a learning innovation. By carrying out an innovation, it is hoped that the quality of learning can be improved. In this study, observing the implementation of geography learning during the pandemic. The research location was conducted at SMAN 1 Subang, SMAN 2 Subang, and SMAN 1 Pagaden. This research is qualitative descriptive, meaning that this research seeks to find interactive patterns of relationships and to gain understanding of meaning. The findings in SMAN 1 Subang, learning that was done virtually was considered less effective, while in SMAN 2 Subang online learning showed better results when compared to face-to-face learning. Online learning at SMAN 1 Pagaden shows good results with the implementation of a project based learning model using google earth media and the whatapps group. As a solution to the problems that arise is to implement the offline model of distance learning as well as the visiting teacher model.